Community Projects Administration (Planning Commission) - Planning Commission (Planning Commission, 1952)
Planning commission community projects administration. Development commissioners’ conference 7th to 13th may, 1952. Main recommendations and conclusions. The community projects administration will arrange for an orientation and training course for project officers in a central place, in or about a project area, from 15th July to 15th August, 1952. The project officer will be responsible for the execution of the work on the community project, and will also co-ordinate other development work in the area. The ordinary agency in charge of development work in the area will not be superseded, but policy will be centralised. The agency may require to be adapted or modified, as circumstances require. The project officer should have necessary and sufficient powers delegated to him. Additional powers may also be needed by the development commissioner and district development officers. State governments will consider these. In certain cases, as may be found convenient by the state government, the district development officer and the project officer may be one and the same person, but it is essential that the officer be stationed in the project area.
Development Commissioners’ Conference On Community Projects May 7th—May 13th, 1952 Summary Record